Hematotoxicity and functional impacts related to chemotherapy with doxorubicin and cyclophosphamide for invasive ductal breast carcinoma: a study in clinical records - Kameo, Simone Yuriko; Ramos, Maria Júlia Oliveira; Lima, Ricardo Barbosa; Amorim, Bruno Ferreira; Costa, Jéssica dos Santos; Marinho, Pabliane Matias Lordelo; Sawada, Namie Okino; Silva, Glebson Moura (Journal of Health & Biological Sciences, 2021)
Objective: To evaluate the occurrence of hematological and functional toxicities during chemotherapy with doxorubicin and cyclophosphamide in women with breast invasive ductal carcinoma. Methods: This was a descriptive, cross-sectional and quantitative study, involving the data collection in clinical records of 119 women undergoing chemotherapy for breast invasive ductal carcinoma in an oncology outpatient clinic, carried out between February 2014 and February 2015. Results: The investigated toxicities and their respectively occurrences in patients exposed to doxorubicin and cyclophosphamide were hemoglobinemia (26,5%), leukopenia (21,6%), neutropenia (10,8%), thrombocytopenia (none) and reduced hematocrit (28,4%), in addition to fatigue (93,1%), fever (20,6%), gain (35,3%) and weight loss (22,5%). In these variables, there were no significant differences between the exposed and not exposed patients. The association with taxanes showed a significant reduction in hematocrit values (p=0.019) and the toxicities distributed by age group were not significant within the exposed group. Conclusions: Exposure to doxorubicin and cyclophosphamide was not associated with an increase in the occurrence of hematotoxicities and functional impacts in women with breast ductal invasive carcinoma, except when associated with taxane agents.